Exotic and invasive species compromise the seed bank and seed rain dynamics in forests undergoing restoration at urban regions - Londe, Vinícius; de Sousa, Hildeberto Caldas; Kozovits, Alessandra R. (Journal of forestry research, 2017)
The control of exotic and invasive species in areas undergoing recovery is a challenge for ecological restoration and this problem may be even greater in urbanized areas. This study evaluated the seed bank and seed rain of a 5-year-old riparian forest located at the metropolitan region of Belo Horizonte in southeast Brazil, and verified changes over time in the abundance and species richness and whether planted species already were providing propagules to the site. At the forest, fifteen parcels of 100 m2 were distributed randomly and soil samples were collected thrice (October 2011, March 2012 and July 2012) to evaluate the seed bank. Seed traps were installed in nine parcels to collect propagules over 1 year.Propagules were segregated and germinate at greenhouse.Species richness and abundance were estimated, and variance and similarity were quantified. In total, 86 species were recorded in the seed banks, 41.9% natives and 33.7% exotics, with the predominance of herbs (87.2%) and only7% of trees. Species classified as weeds amounted to 52.3%. In the seed rain 642 seedlings germinated but they belonged to only 10 species, half of them were exotics.Regarding life forms, half of the species were arboreal anddominated the samples, highlighting the exotic species Melia azedarach. The species richness of the seed bank did not differ by season, unlike the seed rain which varied significantly by month. Seed bank and seed rain species had a very low floristic similarity with the list of planted species, suggesting that few planted trees had dispersed or were stocking propagules. Many non-planted species were recorded, mostly exotics and/or invasive that were probably derived from the surrounding urban matrix. These might interrupt the successional dynamics of the restoration forest and compromise the restoration process in the medium and long-terms. Our results highlight: (1) the importance of monitoring areas undergoing restoration; (2)that restoration methods and management actions directed to control exotic and invasive species are particularly important for sites in urban regions; and (3) the relevance of conserving forest fragments as sources of propagules for nearby areas.